2020
DOI: 10.1097/cm9.0000000000001135
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of early and late drug-eluting stent in-stent restenosis and mid-term prognosis after repeated percutaneous coronary intervention

Abstract: Background: The mechanism and characteristics of early and late drug-eluting stent in-stent restenosis (DES-ISR) have not been fully clarified. Whether there are different outcomes among those patients being irrespective of their repeated treatments remain a knowledge gap. Methods: A total of 250 patients who underwent initial stent implantation in our hospital, and then were readmitted to receive treatment for the reason of recurrent significant DES-ISR in 2016 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, stent implantation in the coronary artery can cause vascular injury and neointimal hyperplasia, leading to the occurrence of in-stent restenosis (ISR). According to reports, the occurrence of ISR in the new generation of drug-eluting stents is still about 3-10% [3,4], and approximately 25% of patients with ISR present with acute myocardial infarction [5]. Although the incidence of ISR is low, considering the large number of people undergoing stent implantation for revascularization and the poor prognosis of ISR, it is crucial to discover groups at high risk for ISR.…”
Section: Introductionmentioning
confidence: 99%
“…However, stent implantation in the coronary artery can cause vascular injury and neointimal hyperplasia, leading to the occurrence of in-stent restenosis (ISR). According to reports, the occurrence of ISR in the new generation of drug-eluting stents is still about 3-10% [3,4], and approximately 25% of patients with ISR present with acute myocardial infarction [5]. Although the incidence of ISR is low, considering the large number of people undergoing stent implantation for revascularization and the poor prognosis of ISR, it is crucial to discover groups at high risk for ISR.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular damage and the ensuing intima inflammation function as the first stimulus for multiplication and stimulation of vascular smooth muscle. As a result, myofibroblast move to create neointimal layer and extracellular matrix that is coated by endothelial cells above the stented section, leading to restenosis of the stent 4 . Additionally, a previous study identified the stent under-expansion as a significant possible ISR mechanism 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the success rate of CTO PCI reaches around 90% owing to the advancements in recanalisation techniques and devices, 1 IS‐CTO PCI always achieves lower success ratios of 63% to 71% 2‐5 mostly due to wire crossing difficulties from the presence of the stent and also potential stent under expansion. As is well known, PCI for non‐occlusive in‐stent restenosis (ISR) yields worse outcomes than those PCI in de novo lesions, even in the era of drug‐eluting stents (DES) 6‐8 . The pre‐existing artificial stent structure results in a considerably worst long‐term outcome for the IS‐CTO lesion than the de novo CTO.…”
Section: Introductionmentioning
confidence: 99%
“…yields worse outcomes than those PCI in de novo lesions, even in the era of drug-eluting stents (DES). [6][7][8] The pre-existing artificial stent structure results in a considerably worst long-term outcome for the IS-CTO lesion than the de novo CTO. IS-CTO has been identified as an independent predictor of target-vessel revascularisation (TVR).…”
mentioning
confidence: 99%